Integration areas between constitutional oversight institutions for investigating the use and management of public funds - Cherif, Badis (The International tax journal, 2025)
Constitutional oversight institutions, such as the Audit Council and High Authority for Transparency and Prevention and Combating of Corruption, are responsible for monitoring state funds, regional collectives, and public services. Article 184 of the 2020 constitutional amendment establishes areas for their integration to enhance their effectiveness in corruption prevention and combating. These bodies' functions extend beyond their possession of resources and legislative and regulatory tools, addressing financial and administrative corruption. Based on the above, this research paper aims to highlight the integration areas that enhance the role of the Audit Council and the High Authority for Transparency and the Prevention and Combating of Corruption. This integration is seen as a crucial mechanism that contributes to the activation of the legislative and regulatory framework for sound governance and the rationalization of public spending.